Modeling the surface and groundwater water flow response to climatic and land use changes on a cascade of rice paddies - Bucton, Bredith Grace B.; Soriano, Mario A. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
With climate change occurring globally, water resources are also affected. The Ifugao Rice Terraces, composed of mountains of rice paddies constructed and maintained by traditional farming, especially stand vulnerable to these changes. It is the aim of this research to model the effects of climate and land use changes to the surface and groundwater hydrology of a system of rice paddies. A site in Kiangan, Ifugao, Philippines was chosen for this study. The catchment was delineated and characterized using GIS processing. Observed temperature and precipitation data from 2010 were adjusted using AJB scenario downscaled climate data to predict the conditions come 2020 and 2050. Land use change was incorporated in the model to reflect the four different planting seasons observed in lfugao. The US Geological Survey Coupled Ground-Water and Surface-Water Flow Model (GSFLOW) was used as the model for this research. A total of 14 scenarios were simulated. Results show that the months of October and November 2020 pose high risks of excess runoff while February 2050 exhibits the highest discharge from the stored water. Interventions were suggested to address these extremes.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Groundwater flow -- Philippines -- Mountain Province; Groundwater flow -- Simulation methods